2019
DOI: 10.1186/s13690-019-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of gestational diabetes mellitus in Africa based on the updated international diagnostic criteria: a systematic review and meta-analysis

Abstract: Background: Gestational diabetes mellitus (GDM) is a major public health problem and threat to maternal and child health in Africa. No prior review has been conducted in Africa using the updated GDM diagnostic criteria. Therefore, this review aimed to estimate the pooled prevalence and determinants of GDM in Africa by using current international diagnostic criteria. Methods: A systematic review and meta-analysis was conducted by comprehensive search of the published studies in Africa. Electronic databases (Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
80
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 73 publications
(158 reference statements)
13
80
4
1
Order By: Relevance
“…Miscarriage during index pregnancy may point to the presence of various endocrine pathologies or poor blood glucose control. These may affect the normal metabolism of insulin, hence predisposing the mother to GDM (30). In line with the findings of this study, Teh et al reported that a history of GDM and BMI of above 35 are two independent risk factors for GDM (31).…”
Section: Discussionmentioning
confidence: 99%
“…Miscarriage during index pregnancy may point to the presence of various endocrine pathologies or poor blood glucose control. These may affect the normal metabolism of insulin, hence predisposing the mother to GDM (30). In line with the findings of this study, Teh et al reported that a history of GDM and BMI of above 35 are two independent risk factors for GDM (31).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, reports on the prevalence of GDM in Egypt (6–8.9%) originate from a few small-scale studies [ 13 , 14 , 15 ]. Nevertheless, this prevalence is considerably lower than the overall stated prevalence of GDM in Africa (13.6%) [ 16 ], and it is less likely to reflect the actual magnitude of GDM in Egypt given that the studies may not be representative of the population—the sample sizes were relatively small (130–700 participants), and estimation of a sample size was not performed in any of these studies. Furthermore, the subjects included were from small cities or rural areas.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Further, a systematic review of the prevalence of GDM in Africa found a pooled prevalence of 13.6% with the prevalence in sub-Saharan Africa (SSA) reported at 9% and 14.8% by different groups. 8 9 …”
Section: Introductionmentioning
confidence: 99%